2011
DOI: 10.1063/1.3588037
|View full text |Cite
|
Sign up to set email alerts
|

Numerical simulation of fluid flow around a vertical-axis turbine

Abstract: A novel, vertical-axis turbine has been designed to meet a specific power-generation need. It is intended that the turbine will provide local electricity to off-grid cellular communication towers. It is intended that the turbine will reduce or eliminate the use of diesel-power generation for these towers and result in a reduction of operating costs and greenhouse gas emissions. The design effort has had two main stages. First, a prototype turbine blade was designed and tested in a large-scale wind tunnel. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 45 publications
(25 citation statements)
references
References 14 publications
1
23
0
1
Order By: Relevance
“…According to literatures, the use of end plates has shown an improvement in the performance of SSWTs [14,20,31]. It is mainly caused by the improved pressure difference between the concave and convex surfaces of SSWT blades.…”
Section: Description Of Blade Profilesmentioning
confidence: 99%
See 2 more Smart Citations
“…According to literatures, the use of end plates has shown an improvement in the performance of SSWTs [14,20,31]. It is mainly caused by the improved pressure difference between the concave and convex surfaces of SSWT blades.…”
Section: Description Of Blade Profilesmentioning
confidence: 99%
“…The performance of the turbine is often measured in terms of torque coefficient (C T ), power coefficient (C P ), and static torque coefficient (C TS ), which are expressed by the following equations [34]: Blockage in the wind tunnel experiments is one of the unavoidable phenomena and thereby this must be taken into account while presenting the experimental results [20,31,32,35,36]. The blockage correction factor (f) is largely dependent on the type of wind tunnel test section used (open or closed type), and the blockage ratio (BR = area of turbine model to the area of test section).…”
Section: Experimental Validation and Blockage Correctionmentioning
confidence: 99%
See 1 more Smart Citation
“…The shear stress transport (SST) κ − ω turbulence model is a two-equation eddy viscosity model combining the advantages of both κ − formulation for free stream flow and κ − ω formulations in the rotor boundary layer [30]. Using this model in CF X12.0 software, Abraham et al [8] have carried out a two-dimensional study on the Savonius rotors. Although there seems to be a general agreement between computational and experimental data, however, the 2D simulation results are over predicting the experimental data.…”
Section: Turbulence Models Vs Mesh Configurationsmentioning
confidence: 99%
“…Among these, several authors have analyzed savonius blade behavior in the presence of valves, or gaps, in the center area of the blades, in order to allow the flow passing from one side of blade to another and thus reducing the drug for the retreating blade. Plourde et al [7] and Abraham et al [8] have analyzed experimentally the behavior of both the end plates and the effects of longitudinal vents aligned with the axis of rotation. Results have shown that use of venting give less improvements of the blade performances if compared to endplate.…”
Section: Introductionmentioning
confidence: 99%